2008
DOI: 10.1016/j.drugalcdep.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of dropout from group therapy among patients with bipolar and substance use disorders

Abstract: Objective-Bipolar and substance use disorders frequently co-occur. Integrated treatment for these disorders has been shown to be effective at reducing substance use, but no study has examined attrition from dual diagnosis group therapy. The current study identified baseline demographic and clinical characteristics that predict treatment dropout among patients with co-occurring bipolar and substance use disorders.Method-Using binary and multivariate analyses, baseline data were analyzed as part of a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
4
11
0
Order By: Relevance
“…Several individuals initially agreed to referral and/or discussed attendance at the group, only to fail to attend any of the sessions offered. Our data agree with other studies that showed that those who refused to participate or who dropped out were younger than those who did attend, including IGT studies (Graff et al , ). In a study of an Internet‐based psychoeducation programme (Nicholas et al , ), about 27% participants, especially younger males, did not complete the intervention offered.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several individuals initially agreed to referral and/or discussed attendance at the group, only to fail to attend any of the sessions offered. Our data agree with other studies that showed that those who refused to participate or who dropped out were younger than those who did attend, including IGT studies (Graff et al , ). In a study of an Internet‐based psychoeducation programme (Nicholas et al , ), about 27% participants, especially younger males, did not complete the intervention offered.…”
Section: Discussionsupporting
confidence: 92%
“…Attendance rates are a useful proxy measure of engagement, and it was encouraging that all six individuals who began the group programme attended at least five M1 sessions, and four out of the six also attended five or more sessions of M2; only one individual dropped out. This attrition in group membership is similar to the 19–21% reported in studies of integrated therapy (Graff et al , ; Wenze et al , ). Intermittent absenteeism from planned sessions has been partly resolved in other studies through the use of automatic text‐messaging (Graff et al , ).…”
Section: Discussionsupporting
confidence: 82%
“…However, despite the small sample size, our final model afforded strong and reliable prediction of clinical trial dropout. Furthermore, as noted by Graff and colleagues (2008), those who did drop out of the study may represent an especially difficult to retain population. Our preliminary results suggest that it may be possible to identify patients at high risk of clinical trial dropout who could benefit from new and/or intensified retention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Following the method used previously in a similar sample (Graff et al 2008), dropout was defined as missing at least the last 4 weekly study visits. Group differences on baseline characteristics were evaluated using chi-square and independent sample t-tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation